Low rate of germline AIP mutations in patients with apparently sporadic pituitary adenomas before the age of 40: a single-centre adult cohort. - Preda, V; Korbonits, M; Cudlip, S; Karavitaki, N; Grossman, AB (BioScientifica Ltd., 2014)
AIM: To study the prevalence of germline mutations of the aryl-hydrocarbon receptor interacting protein (AIP) gene in a large cohort of patients seen in the Oxford Centre for Diabetes Endocrinology and Metabolism (OCDEM), UK, with apparently sporadic pituitary adenomas, who were either diagnosed or had relevant clinical manifestations by the age of 40 years. PATIENTS: We prospectively investigated all patients who were seen at Oxford University Hospital, OCDEM, and a tertiary referral centre, between 2012 and 2013, and presented with pituitary tumours under the age of 40 years and with no family history: a total of 127 patients were enrolled in the study. METHODS: Leukocyte-origin genomic DNA underwent sequence analysis of exons 1-6 and the flanking intronic regions of the AIP gene (NM_003977.2), with dosage analysis by multiplex ligation-dependent probe amplification. RESULTS: AIP variants were detected in 3% of the 127 patients, comprising four of 48 patients with acromegaly (8%), 0 of 43 with prolactinomas, 0 of the 20 patients with non-functioning adenomas, 0 of 15 with corticotroph adenomas and 0 of one with a thyrotroph adenomas. Definite pathogenetic mutations were seen in 2/4 variants, comprising 4.2% of patients with acromegaly. CONCLUSIONS: This prospective cohort study suggests a relatively low prevalence of AIP gene mutations in young patients with apparently sporadic pituitary adenomas presenting to a tertiary pituitary UK centre. Those with somatotroph macroadenomas have a higher rate of AIP mutation. These findings should inform discussion of genetic testing guidelines.